Study and Implementation of the Fuzzy Mamdani and Sugeno Methods in Decision Making on Selection of Outstanding Students at the South Aceh Polytechnic - Amsar Yunan; Muhammad Ali (LPPM Politeknik Aceh Selatan, 2020)
The selection of students who excel academically is a measure of the quality of education in an educational institution. In the implementation of education, student achievement becomes a measure of the success of education at the institution. Achievement is the result of hard work by following the rules given by a certain person or institution with certain criteria and conditions to determine if someone is eligible to be chosen as an award recipient. This research uses the Mamdani Fuzzy method or Fuzzy inference system and Sugeno Fuzzy, to design this decision-making system is to design the decision results from the rules compiled using Matlab software for testing. The South Aceh Polytechnic holds outstanding student elections every year, the selection of students with achievements that are carried out every year only focuses on the GPA value in academic achievement without looking at the determining factors which are more precise. In the research that will be conducted the selection must meet the eligibility criteria as a student who gets an award or as an outstanding student at the South Aceh Polytechnic involving variables in the form of Cumulative Achievement Index, Final Project value, Extracurricular, and Attendance. Research is expected to be a tool in the selection process for candidate participants who compete in the selection of outstanding students at the South Aceh Polytechnic so that relevant departments in universities can determine the eligibility of prospective students as award recipients as students with the best achievement scores by considering the appropriate determining factors. The expected output using the Mamdani and Sugeno fuzzy method can become an intellectual property system so that this system can be selected as a guideline by the South Aceh Polytechnic academic for determining outstanding students. The results of the research that have been obtained show that the level of truth is 86.82% for the Mamdani method while the implementation of Sugeno Fuzzy logic is obtained a level of truth of 71.88%